DEVELOPMENT OF TRADITIONAL CAKE MICRO BUSINESS "LARIS" IN MENUR PUMPUNGAN SURABAYA - Kunto Inggit Gunwan; Mataji Mataji (ABDIMAS, 2022)
Since enactment Public Economy ASEAN (MEA) on end year 2015 should encourage all economic actors without exception SMEs and Micro Enterprises to improve themselves in order to improve the quality of production of both goods and services. If not done, then Indonesia is a "soft" market for Asean countries other because of Indonesia has the largest population ( population size ) in Asean, namely no less 270's million soul population. SMEs and Effort Micro which is embodiment people's economic democracy, is very hard hit when the flow of goods and services is so swift from various Asean countries invaded the Indonesian market. Realizing that doing strengthening ( empowered ) to SMEs and Effort Micro is a must and the necessity of being able to find a national identity that has a comparative advantage and competitive advantage . This activity begins with identifying existing land issues and next looking for method the solution, method which used is with provide training and assistance. The results that have been achieved are the ability traditional cake business optimizing sales with use local raw materials. With thereby Effort Micro Traditional Cake " selling" could increase ability in the field production and management effort. Existence outside the as indication enhancement empowerment effort.